Improving assisted living care. - Gregory N; Gesell SB; Widmer T (Journal of Nursing Care Quality)
In the absence of a national measurement system, private vendors of satisfaction measurement and improvement services have played a crucial role in the quality movement in the assisted living industry. Survey responses from 175 resident-family dyads at 20 facilities were analyzed to identify priorities for service improvement from the customers' perspective. They include improving care provided by aides and management, meal service, and activities. Practical solutions for addressing these issues are presented.